Prostitution, Crime, and Law Enforcement: Criminology Studies in the Argorejo Resocialization and Rehabilitation of Semarang City (Law Research Review Quarterly, 2020)
Prostitution is a complex social problem, remembering prostitution is the oldest civilization that still exists in our society. Often prostitution is classified by our society for commercial purposes solely with women who are immoral, cannot stand the faith and various antipathy attitudes towards prostitutes who for various reasons enter the dark world regardless of the relation to various aspects of people's lives with prostitution. The factor in prostitution is that most of the problems lie in economic and social factors. The main factor is the lack of physical well-being, including the sense of security and peace that can be achieved if public awareness of the obligation to respect the rights of others has been understood and internalized so that the enforcement of law and justice is based on truth which is the needs of others, all members of society. The difficulty to meet the needs of a handful of women (skill), taking shortcuts by peddling themselves in certain places, seems to be a disheartening view. Even though they know the consequences of their actions, they do not deter them or think further about the consequences of the prostitution problem.In connection with prostitution, the Criminal Code regulates it in two articles, namely Article 296 and Article 506. The Criminal Code makes intentions causing or facilitating acts of violating decency with third people as livelihoods or as a custom regulated in Article 296 of the Criminal Code. Article 506 of the Criminal Code is regulated as a criminal act as a pimp.